Factors influencing customer loyalty towards MILO products / Ena Suhaila Abas - Abas, Ena Suhaila (Faculty of Business and Management, 2008)
The cost of selling to new customers is higher than the cost of selling to existing customers. Therefore, it is important for the company to foster customer loyalty in order to create long-term relationship and repurchasing decisions. In this study, customer loyalty towards MILO products becomes a major topic to be discussed. Factors such as product quality, corporate image, trust and customer switching cost have been identified in order to investigate whether or not these factors have significant relationship with customer loyalty. Later to determine the level of customer loyalty and the most influence factors towards MILO products.